Sea ice climatology in the Canadian Western Arctic: thermodynamic versus dynamic controls. (9th July 2014) - Candlish, L. M.; Iacozza, J.; Lukovich, J. V.; Horton, B.; Barber, D. G.
ABSTRACT Based on the regions in the western Canadian Arctic as outlined by the Canadian Ice Service, the normals and trends from 1981 to 2010 were analysed for the monthly surface air temperature, monthly wind speed and direction. For the month of September, the temperatures from 1981 to 2010, for all of the defined regions, increased by 2–4 °C. The monthly concentrations of sea ice and multiyear ice were analysed for normals and trends from 1981 to 2010. Although the whole Arctic has seen a large reduction in the minimum sea ice extent, in the defined region of study during September, only the Beaufort Sea region shows a statistically significant decrease in sea ice concentrations. Correlations between the climatological state variables and sea ice were investigated in this study to determine relative thermodynamic and dynamic contributions to a decline in sea ice extent in the Western Arctic. As expected, the regions of interest all showed a statistically significant correlation between the surface air temperatures and the total sea ice concentrations. However, neither the wind speed nor the direction had a strong correlation on the sea ice concentration trends. This study showed that in the regions investigated, thermodynamic forcing of sea ice is the dominant driver when compared with dynamic forcing, which is a secondary driver in the western Canadian Arctic.